Efforts to Improve Teacher Competence in Mastering Google Forms Through Peer Tutorial Programs at SD Negeri Bojonggede 01, Bojonggede District, Bogor Regency - Chandra Sagul Haratua; Arini Widya Pratiwi (Syntax Corporation Indonesia, 2023)
This research was conducted at SD Negeri Bojonggede 01 which aimed to determine the implementation of peer tutorial programs in mastering Google Forms. The subjects of this study were all teachers of SD Negeri Bojonggede 01 as many as 26 teachers, with 4 male and 22 female teachers. The collection of assessment data is carried out by observation through questionnaires. The results of this study can be concluded that, in the condition of teachers before there was a peer tutorial program, only 20.3% knew the Google Form application. While the expected conditions only amount to 50% of the number of teachers. However, after the peer program, many teachers who have understood and were able to achieve success in making online attendance through Google Form and applying it to online learning totaled 20 teachers (76.9%). This still needs to be improved again with the efforts of teachers to be more intensive in habituating routine activities for teaching and learning through the Google Form application.